Implementation of The Steam Approach in Supporting Free Learning - Khodijah Robiatul Adawiyah, Siti; Jannah, Miftachul; Kusnandar, Enan (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
Implementation of the STEAM Approach in Supporting Independent Learning (Case Study at Bunga Tanjung Kindergarten, Pondoksalam District, Purwakarta Regency). Freedom to learn is a policy that was issued in 2020. The essence of free learning is so that teachers and children can face 21st-century education and the 4.0 industrial revolution. However, long before the policy of independent learning was issued, the independence of learning for early childhood education programs level had been realized in the concept of learning through play because learning through play was the same as learning freedom. One approach that can be used to support independent learning is to use the STEAM approach. Because STEAM is an approach that can deal with 21st-century education and the 4.0 industrial revolution, this study aims to describe: (1) the implementation of the STEAM approach in supporting independent learning, (2) the supporting and inhibiting factors, advantages and disadvantages, and the effectiveness of the implementation of the STEAM approach in supporting independent learning. This study uses a qualitative approach, and data collection is done using observation, interviews, and documentation. The data analysis used is the Miles and Huberman model, where the process starts from reducing the data, then presenting the data and verifying it. The data validity technique used is the source triangulation method. The results show that the implementation of the STEAM approach in supporting independent learning has been carried out starting from the curriculum, which includes plans, methods, models, strategies, evaluations, and infrastructure, as well as the steps in the RPPH so that everything shows that STEAM can support free to learn.